Enterprise Architecture Planning at the Health Sciences Faculty of UMSurabaya Using the Zachman Framework - M. Taufiqur Rohman; Made Kamisutara; Muhammad Mustajib (Politeknik Dharma Patria Kebumen, 2021)
Health Sciences Faculty of Muhammadiyah University of Surabaya (UM Surabaya) is a faculty in UM Surabaya. It has a mission to develop academic, general, and student administration services based on quality management systems and the application of Information Technology. To achieve the mission, it is necessary to design and implement Information Technology in assisting administrative service business processes including a letter management system, the attendance system of staff and lecturer, and a financial submission system for the activity plan of the Implementing Unit, Head of Study Program, and Quality Control Group at the Faculty of Health Sciences UM Surabaya. Therefore, this research aimed to build an Enterprise Architecture Planning (EAP) using Zachman Framework method. This research resulted a structured integrated information system Blueprint design along with application prototypes at the Faculty of Health Sciences UM Surabaya. With the Information System Blueprint design, it made it easier for Developers to develop information systems and documented every system transaction process.